Thermodynamic characterization of DNA Triple-Helical three-way junctions - Hüsler, Paul L (Department of Molecular and Cell Biology, 2016)
Watson-Crick CWC) and Hoogsteen (HG) triple-helical three-way junctions were constructed from three 33-mer oligonucleotides. The same sub-set of sequences have been used in the arms of the junctions. The junctions differ primary in the arrangement of the branch point and the ends of the arms. In the case of the HG triple-helical three-way junction, the three 33-mer oligonucleotides can fold into hairpin structures, linked by a four membered cytosine loop. Each of the hairpins contain a homo-pyrimidine 10-mer single strand extension which interacts with a neighboring hairpin to form a triple-helix on lowering the pH (between 6 and 4), via Hoogsteen (HG) hydrogen bonding. Collectively this process results in the formation of the branch point and the triple-helical arms. In the case of the WC triple-helical three-way junction, the three 33-mer oligonucleotides interact with a neighboring oligonucleotide to form a duplex. Collectively this process leads to the formation of a double-helical three-way junction with each arm containing a 9-mer homo-pyrimidine extension connected by four cytosines. Each of the single strand extensions can mutually fold back onto the duplex arms converting each arm into a triplex. The WC and HG triple-helical three-way junctions were characterized by gel electrophoresis, temperature gradient gel electrophoresis, circular dichroism (CD), uv melting, and differential scanning calorimetry (DSC). In both structures; arm A contained exclusively TAT triad bases, while arms B and C contained an increasing number of CGC+ triads, respectively. To counteract possible crowding at the branch point the 5' sequence was shortened by one base. The assembly of the completely folded structure was found to be spontaneous if an appropriate ionic strength and pH range was chosen. A separate set of isolated arms has been investigated to elucidate the role each arm plays in the complete structure. Comparing the summed-up properties of these arms with the data obtained for the integral three-way junctions, it is obvious that the we three-way junction is partly distorted at the branch point, in line with observation obtained from double-helical three-way junctions, while the HG threeway junction is completely ordered. A set of mathematical models has been developed to describe the thermal unfolding of the multi-strand DNA structure and to identify the intermediate states. Presented is a formalism, starting from the grand partition function, that describes the effects of pH on the thermal stability of triple-helices. The formalism can be used over a wide pH range. It covers nearest neighbor electrostatic effects of closely spaced cytosines in the Hoogsteen and Watson & Crick strands. A procedure is employed to predict enthalpy and entropy changes for triplex formation. The obtained values are in good agreement with the results obtained by differential scanning calorimetry. It is the first time that multistrand, branched DNA structures of this complexity were constructed, completely described, and characterized thermodynamically.